Examining Farmers' Knowledge and Participation in the Cattle and Buffalo Business Insurance Program in Timbuseng Village, South Sulawesi, Indonesia - Tenrisanna, Vidyahwati; Kasim, Kasmiyati; Lestari, Veronica Sri; Qinayah, Mirnatul (Jurnal AGRISEP, 2026)
The Cattle and Buffalo Business Insurance (CBBI) program, launched by the Indonesian government, aims to provide financial protection to smallholder farmers against livestock deaths or losses. This study investigates the impact of farmers' knowledge on their engagement with the CBBI program in Timbuseng Village, situated in the North Polongbangkeng District of Takalar Regency, South Sulawesi, Indonesia. A cross-sectional descriptive quantitative analysis was conducted using primary data collected through structured questionnaires from a sample of 74 beef cattle farmers. Fisher's exact test was employed in a bivariate analysis to evaluate the link between farmers' understanding of CBBI objectives, registration procedures, premiums, and claim procedures and their participation in the program. All data were processed using STATA 14.2 software. The study findings reveal a robust and statistically significant correlation between the four types of knowledge about the CBBI program and their involvement in the program. Addressing knowledge gaps and simplifying processes could enhance CBBI program adoption to support sustainable livestock production and strengthen smallholder farmers' resilience in Indonesia.